The South as a transfeminist territory and a situated figuration - María Angélica Vega (Estudios de Teoría Literaria)
In this article, we work with a group of transfeminist thinkers and activists from the South who have been reflecting on space in recent years, including Rita Segato, Nelly Richard, Judith Butler, val flores, Andrea Giunta, Verónica Gago, Fernanda Carvajal, Nora Domínguez, Cecilia Palmeiro, Ana Longoni, Iliana Diéguez, María Moreno and Donna Haraway. First, based on some of their interventions, we are interested in presenting how they think about two notions central to contemporary Latin American transfeminist thought and activism: territory and the South. Second, we address their positions on a contemporary transfeminism that is trans and plurinational, that is, one that is not limited to the territorial boundaries of Nation-States. Finally, we address the figure of the fugitive from val flores as a mode of tactical intervention in and from the representation of the southern territory.